Enxertia e água de irrigação carbonatada no transporte de 15N e na produção do tomateiro - Branco, Roberto B. F. [UNESP] (2007)
The effects of CO2 application through irrigation water, and of grafting in transport of 15N and in the tomato production, were studied. These treatments were arranged in a 2 x 2 factorial scheme (with and without CO2 in irrigation water and grafted and non-grafted tomato), in a completely randomized design, with four replications. The injection of CO2 into the water began at 34 days after transplant of seedlings (DAT) and continued for all irrigations. The application of the sulfate of ammonium with abundance in atoms of 15N of 3.13% in plants destined to analysis was done at 45 DAT when the plants were in the middle of fructification. After 14 days of fertilizer (15N) application the plants were harvested, washed, dried and sent for analysis of 15N in plant tissue. The results demonstrated that CO2 and the grafting did not alter the transport of 15N in the plant. The production of commercial fruits was larger when CO2 was applied in water.